Evaluasi Implementasi Kebijakan Pemberian Persetujuan Pembangunan Rumah Ibadah Di Wilayah Kota Administrasi Jakarta Utara - Mohadi Mohadi; Pandoyo Pandoyo (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The research aims to identify the “Evaluation of Religious Buildings Construction Approval Policy Implementation in North Jakarta Administrative City Area The research describes and explains the existing phenomenon in detail using the descriptive-qualitative analysis method and interview technique as the supporting investment. The study on the Evaluation of Religious Buildings Construction Approval Policy Implementation in North Jakarta Administrative City Area found that implementation is exemplary. However, some improvements in the service quality are still needed. Some of the obstacles encountered were lack and incompetence of human resources in its field. And to overcome this is by improving existing human resources, expanding the existing personnel, and continuous awareness efforts in the community.